Pengaruh Media Pembelajaran Bahan Tayang Berbasis Kearifan Lokal Temanggung Terhadap Hasil Belajar Matematika - Laila Nur Latifah; Hamidulloh Ibda; Muhammad Fadloli Al-Hakim (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2023)
This study aims to determine the effect of the implementation of PPT learning media based on Temanggung local wisdom on the mathematics learning outcomes of grade II students of MI Salafiyah Kranggan, Temanggung Regency in the 2021/2022. The research approach is quantitative with a quasi-experimental method with a pre test and post test control group design with a purposive sampling system. The research subjects were grade II students of MI Salafiyah with two study groups, namely control class II A, and experimental class II B. The treatment in the two classes was differentiated by the application of a control group pre test and post test design. The treatment in both classes was differentiated by the application of PPT learning media based on Temanggung local wisdom in the experimental class, while the control class did not. The instruments used were tests with a total of 30 items and observation sheets. The results showed that: (1) the material prepared is in accordance with the objectives, the features of learning media make it easier for teachers and students in learning and the quality of learning media can produce fun, innovative, effective, creative classes, and active students in learning, and (2) there is an effect of PPT learning media based on Temanggung local wisdom on the math learning outcomes of grade II students of MI Salafiyah Kranggan, which is indicated by the value of tcount> ttable or 3.410> 2.120 and sig. (2-tailed) = 0.004 <0.05. It is evident that the experimental class post test results have increased by 14%, with the pre test value obtaining an average of 69 after treatment and the average post test value obtained is 83